Interactions between key genes and pathways in prostate cancer progression and therapy resistance - Wu, Fan; Zhang, Hengsen; Hao, Miaomiao (Frontiers in Oncology, 2025)
Prostate cancer is one of the most prevalent malignant tumors in men, particularly in regions with a high Human Development Index. While the long-term survival rate for localized prostate cancer is relatively high, the mortality rate remains significantly elevated once the disease progresses to advanced stages, even with various intensive treatment modalities. The primary obstacle to curing advanced prostate cancer is the absence of comprehensive treatment strategies that effectively target the highly heterogeneous tumors at both genetic and molecular levels. Prostate cancer development is a complex, multigenic, and multistep process that involves numerous gene mutations, alteration in gene expression, and changes in signaling pathways. Key genetic and pathway alterations include the amplification and/or mutation of the androgen receptor, the loss of Rb, PTEN, and p53, the activation of the WNT signaling pathway, and the amplification of the MYC oncogene. This review summarizes the mechanisms by which these genes influence the progression of prostate cancer and highlights the interactions between multiple genes and their relationship with prostate cancer. Additionally, we reviewed the current state of treatments targeting these genes and signaling pathways, providing a comprehensive overview of therapeutic approaches in the context of prostate cancer.